2009
DOI: 10.1080/03098260902734943
|View full text |Cite
|
Sign up to set email alerts
|

Demystifying Academic Writing: Reflections on Emotions, Know-How and Academic Identity

Abstract: Writing is the foundation of academic practice, yet academic writing is seldom explicitly taught. As a result many beginning (and experienced) academics struggle with writing and the difficult emotions, particularly the self-doubt, that writing stirs up. Yet it need not be like this. In this paper, strategies are discussed for attending to the emotions of writing, and developing writing know-how and a stronger sense of identity as a writer. It is argued that addressing all three aspects of writing-emotions, kn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
100
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 105 publications
(105 citation statements)
references
References 15 publications
5
100
0
Order By: Relevance
“…The transition into an academic role has been identified as challenging even for experienced scholars, with individuals doubting their credibility and competence (Boyd and Harris, 2010). This experience has been echoed by writers who fear being exposed as 'frauds', with feelings of perfectionism and shame towards their writing (Grant and Knowles, 2000) many academics and research students experience writing-related struggles (Caffarella and Barnett, 2000;Cameron et al, 2009) with reported concerns of having their inadequacies exposed in their published writing. These anxieties are often compounded in applied disciplines where individuals are accomplished exponents of their craft but often less confident about their academic scholarship.…”
Section: Background/literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…The transition into an academic role has been identified as challenging even for experienced scholars, with individuals doubting their credibility and competence (Boyd and Harris, 2010). This experience has been echoed by writers who fear being exposed as 'frauds', with feelings of perfectionism and shame towards their writing (Grant and Knowles, 2000) many academics and research students experience writing-related struggles (Caffarella and Barnett, 2000;Cameron et al, 2009) with reported concerns of having their inadequacies exposed in their published writing. These anxieties are often compounded in applied disciplines where individuals are accomplished exponents of their craft but often less confident about their academic scholarship.…”
Section: Background/literature Reviewmentioning
confidence: 99%
“…Increased confidence is a commonly cited outcome of writing interventions as they encourage feelings of greater capability and growing identity as a writer. Cameron et al (2009), Grant (2006 and Moore (2003) all refer to growth in participants' self-belief as writers. Writing therefore, may become less daunting and the mystery surrounding writing for publication diminished, via a collaborative, 'enclosed' facilitative event (Aitchison and Lee, 2006).…”
Section: Background/literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Simply discovering that all candidates experience difficulties and self-doubt during candidature seems to have alleviated some of our anxiety; as Cameron, Nairn and Higgins (2009) and Wellington (2010) remind us, these are common but often unspoken emotional concerns for many PhD students. The understanding that 'others in the same situation are struggling with the same problems as I do' can also be crucial for developing confidence as an early career academic.…”
Section: Struggling With Self-doubtmentioning
confidence: 99%
“…Bosanquet and Cahir [67] show how this is particularly relevant to doctoral students who are developing their identities as writers and scholars. Emotions surface because of the "intensely personal relationship with the self during the writing process" [68] (p. 272). Feelings of self-doubt, anxiety and dread are often experienced by doctoral students.…”
Section: Emotional Tensionsmentioning
confidence: 99%